Philosophical Foundations of Islamic Economics: The Formation of Islamic Economics from the Perspectives of Epistemology, Ontology, and Axiology - Nur Halimah (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
The Islamic economy presents different challenges than conventional economics. Beyond monitoring the behavior of economic actors, including producer households, consumer households, and the government, the challenge is to develop a concept of ideal behavior according to Islamic teachings that economic actors should adopt and its potential impact on the economy. Specifically, this science, in addition to studying relevant variables that can cause differences between actual and ideal behavior, also proposes appropriate strategies to guide one's actions. Ontology discusses the nature of the object of study. In other words, ontology is the science of existence itself. Epistemology examines how knowledge systems are structured. In other words, it discusses the scope and limitations of science. Revelation's truth is not arbitrary, and its role in seeking truth is crucial because it is absolute. However, rational truth and empirical facts must be placed within the overall Islamic framework. In fact, Islam highly values reason, and God is angry with those who refuse to use reason. The study of the axiology of Islamic economics aims to examine Islamic economics from the perspective of values and interests. The existence of Islamic economics is expected to provide solutions to these problems.